ON THE MANUSCRIPT COPIES AND PUBLICATION OF MIFTAḤ AL-ADL - Muhammadsoliyev Sayfulloxon Hidayatilla o‘g‘li (Western European Studies, 2025)
This study explores the manuscript tradition and modern publication history of Miftaḥ al-Adl, a significant work in Islamic jurisprudence and theology. It examines the extant manuscript copies, their geographical distribution, paleographic features, and textual variations. The research also addresses the editorial practices applied in the preparation of printed editions, highlighting critical issues such as transcription accuracy, commentary inclusion, and the preservation of the author’s original intent. By analyzing the historical transmission of Miftaḥ al-Adl, the study contributes to the broader understanding of Islamic scholarly heritage, manuscript preservation, and the challenges of modern publication of classical Islamic texts.
Keywords: Miftaḥ al-ʿAdl; islamic jurisprudence; manuscript tradition